2021
DOI: 10.3389/fmed.2021.766841
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Intervention on Peripheral Skeletal Muscle in Stable Patients With COPD: A Systematic Review and Meta-Analysis

Abstract: Objectives: Peripheral skeletal muscle dysfunction is an important extrapulmonary manifestation of chronic obstructive pulmonary disease (COPD) that can be counteracted by exercise training. This study aimed to review the effect of three major exercise training modalities, which are used in pulmonary rehabilitation to improve on skeletal muscle mass, function, and exercise capacity in COPD.Methods: PubMed, Embase, EBSCO, Web of Science, and the PEDro database were searched on April 25, 2020. Only randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 61 publications
4
10
0
Order By: Relevance
“…Consistent with previous findings on muscle strength 24 , significant heterogeneity characterizes the training programs and testing procedures of the studies included in this systematic review. Most training programs were scheduled for outpatients with COPD over two to three sessions a week for a minimum of eight weeks.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with previous findings on muscle strength 24 , significant heterogeneity characterizes the training programs and testing procedures of the studies included in this systematic review. Most training programs were scheduled for outpatients with COPD over two to three sessions a week for a minimum of eight weeks.…”
Section: Discussionsupporting
confidence: 83%
“…Previous reviews addressed the impact of various exercise-based interventions on different outcome measures of muscle function in persons with COPD [21][22][23][24]. However, the effects of exercise training on skeletal muscle power are yet to be explored, and a systematic review is needed to investigate the current COPD-related literature on this topic.…”
Section: Muscle Power In Patients With Chronic Obstructive Pulmonary ...mentioning
confidence: 99%
“…Likewise, the effects of exercise training on increasing measures related to muscle or fat-free mass in COPD are inconsistent, as reported in two previous systematic reviews (18,19). Despite the prominence of nutritional supplementation and exercise training as methods to increase measures of fat-free mass in COPD, which have been the focus of previously discussed reviews, little is known about other interventions and their potential benefit.…”
Section: Introductionmentioning
confidence: 99%
“…During this session, engage the relevant limb muscles by flexing the knee and hooking the foot to prevent and improve muscle atrophy. Modern research has demonstrated that, with regard to skeletal muscle, appropriate exercise training can have an effect on peripheral skeletal muscle strength and limb mobility [ 25 ]. Simultaneously, the majority of anti-fibrotic IPF patients died of chronic respiratory failure; skeletal muscle loss is observed in these individuals, but there is no significant weight loss, which displays that preventing skeletal muscle atrophy in IPF patients is crucial [ 26 ].…”
Section: Introductionmentioning
confidence: 99%